Infant rhinitis and watery eyes predict school-age exercise-induced wheeze, emergency department visits and respiratory-related hospitalizations - Savary, Khalil W. (Ann Allergy Asthma Immunol, 2018)
BACKGROUND: Rhinitis and conjunctivitis are often linked to asthma development through an allergic pathway. However, runny nose and watery eyes can result from non-allergic mechanisms. These mechanisms can also underlie exercise-induced wheeze (EIW), which has been associated with urgent medical visits for asthma, independent of other indicators of asthma severity or control. OBJECTIVE: Test the hypothesis that rhinitis or watery eyes without cold symptoms (RWWC) in infancy predict development of EIW and urgent respiratory related medical visits at school-age, independent of seroatopy. METHODS: Within a prospective birth cohort of low-income, urban children (n=332), RWWC was queried during the first year of life. Relative risks (RR) for EIW, emergency department (ED) visits and hospitalizations for asthma and other breathing difficulties at age 5–7 years were estimated with multivariable models. Seroatopy was determined at age 7. RESULTS: Infant RWWC was common (49% of children) and predicted school-age EIW (RR=2.8, P<0.001), ED visits (RR=1.8, P=0.001) and hospitalizations (RR=9.8, P=0.002). These associations were independent of infant wheeze. They were also independent of birth order, an indicator of increased risk of exposure to viruses in infancy, and infant ear infections, an indicator of sequelae of upper-airway infections. The association between infant RWWC and age 5–7 ED visits was attenuated (RR=1.2, P=0.23) when age 5–7 EIW was included in the model, suggesting EIW mediates the association. Adjustment for seroatopy did not diminish the magnitudes of any of these associations. CONCLUSION: These findings suggest a non-allergic connection between infant non-wheeze symptoms and important consequences of urban respiratory health by school-age through EIW.